138 Prenatal stress alters genes in signaling pathways influencing behavior and stress response by differential methylation of DNA. (7th December 2018) - Littlejohn, B; Price, D; Neuendorff, D; Carroll, J; Vann, R; Riggs, P; Riley, D; Long, C; Welsh, T; Randel, R
Abstract: The objective of this experiment was to examine differential DNA methylation as a mechanism of altered temperament and stress response in young Prenatally Stressed (PNS) compared with Control bull calves. Mature Brahman cows (n = 48) were transported for 2-h periods at 60 ± 5, 80 ± 5, 100 ± 5, 120 ± 5, and 140 ± 5 d of gestation or maintained as non-transported Controls (n = 48). Methylation of DNA from white blood cells from a subset of 28-d-old intact male offspring (n = 7 PNS; n = 7 Control) was assessed via reduced representation bisulfite sequencing methods. Increased DNA methylation of gene promoter regions typically results in decreased transcriptional activity of the corresponding gene. Therefore, differentially methylated ( P ≤ 0.05) CG sites (cytosine followed by a guanine nucleotide) located within promoter regions (n = 1, 205) were used to predict (using Ingenuity Pathway Analysis software) alterations to canonical pathways in PNS compared with Control bull calves. Among the altered signaling pathways related to behavior and stress response were: opioid signaling, GABA receptor signaling, dopamine-DARPP32 feedback in cAMP signaling, corticotropin-releasing hormone signaling, dopamine receptor signaling, serotonin receptor signaling, and alpha-adrenergic signaling. Among differentially methylated genes ( P ≤ 0.05) related to behavior and stress response were OPRK1, OPRM1, PENK, POMC, NR3C2, TH, ADRA1A, DRD1, DRD5, COMT, HTR6, HTR5A, GABRA4, GABRQ, GAD2, SLC6A11, and SLC6A12 . Alterations to behavior and stress response related genes and canonical pathways supported previously observed elevations in temperament and increased circulating concentrations of cortisol through weaning in the larger population of PNS calves from which bulls in this study were derived (J. Anim. Sci. 94:2:602–609). Differential DNA methylation and predicted alterations to behavior and stress response related pathways in Prenatally Stressed compared with Control bull calves suggest epigenetic programming of behavior and stress response in utero .